Bubbles and Financial Professionals. (28th August 2019) - Weitzel, Utz; Huber, Christoph; Huber, Jürgen; Kirchler, Michael; Lindner, Florian; Rose, Julia
Abstract: The efficiency of financial markets and their potential to produce bubbles are central topics in academic and professional debates. Yet, little is known about the contribution of financial professionals to price efficiency. We run 116 experimental markets with 412 professionals and 502 students. We find that professional markets with bubble drivers – capital inflows or high initial capital supply – are susceptible to bubbles, although they are more efficient than student markets. In mixed markets with students, bubbles also occur, but professionals act as price stabilizers. We show that heterogeneous price beliefs drive overpricing, especially in bubble-prone market environments. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.